Changes in Student Learning Patterns Due to Dependence on Quick Search Technology - Sa'adah, Tanalina Lilatus; Al Qoyyim, Mutawalli Asya'rowi; Pambayun, Balqis Zurin Novara (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2025)
This article examines the significant shift in students' learning patterns caused by fast search technologies such as Google Search. The ease of accessing information has shifted learning from profound discovery to instant information retrieval, a phenomenon known as the